2018
DOI: 10.24326/asphc.2018.1.5
|View full text |Cite
|
Sign up to set email alerts
|

ROOTING SHOOTS OF APPLE VARIETIES AND THEIR TETRAPLOIDS OBTAINED BY THE in vitro TECHNIQUE

Abstract: For breeding purposes, the number of neo-tetraploids of apple cultivars have been derived by in vitro technique. The first attempts at rooting and acclimatization of tetraploid shoots failed. The aim of the study was to develop an effective method for rooting microcuttings of apple neo-tetraploids. In the first stage of the study, in vitro rooting method was optimized for the shoots of diploid donor cultivars. Shoots were rooted on Murashige and Skoog [1962] (MS) medium with a reduced content of nitrogen, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…During the last decade, meta -topolin has been widely used in micropropagation of many plant species, improving multiplication and rooting efficiency [ 41 , 42 , 43 ]. Our previous observation showed that the shoot of rhubarb ‘Malinowy’ treated with meta -topolin had higher rooting capacity than those cultured in BAP medium before rooting (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, meta -topolin has been widely used in micropropagation of many plant species, improving multiplication and rooting efficiency [ 41 , 42 , 43 ]. Our previous observation showed that the shoot of rhubarb ‘Malinowy’ treated with meta -topolin had higher rooting capacity than those cultured in BAP medium before rooting (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…When two strains (EEL16010B and EEL37810) of Rhizobia were used, 100% rooting of Marubakaido rootstock was achieved (Muniz et al 2013). Podwyszyńska and Cieślińska (2018) found that the use of putrescine, a polyamine, when used in combination with NAA and IBA, was able to improve the rooting and subsequent acclimatization of neo-tetraploids of four apple cultivars, 'Free Redstar', 'Gala Must', 'Pinova' and 'Redchief' (more details in Table 2). Phloroglucinol (PG), a phenol derivative, has been successfully employed for the in vitro rooting of many plants including apple, a species that is generally considered to be difficult to root (Webster and Jones 1989;Sharma et al 2000; and is as or even more effective than commonly used auxins (Dobránszki and Teixeira da Silva 2010).…”
Section: Rooting and Acclimatizationmentioning
confidence: 99%
“…The substitution of BAP with meta-topolin enabled the multiplication of the obtained tetraploids and their rooting in vitro as well as acclimatization in the greenhouse. During the last decade, this cytokinin has widely been used in micropropagation of many plants improving not only multiplication rate and shoot quality, but also rooting ability and acclimatization efficiency (Wojtania, 2010;Podwyszyńska, Cieślińska, 2018). The positive effect of this cytokinin was ascribed to its fast metabolism in plant tissue (Werbrouck et al, 1996).…”
Section: Discussionmentioning
confidence: 99%